2022
DOI: 10.3390/cells11243965
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Advanced Melanoma: Treatment Management Implications

Abstract: Artificial intelligence (AI), a field of research in which computers are applied to mimic humans, is continuously expanding and influencing many aspects of our lives. From electric cars to search motors, AI helps us manage our daily lives by simplifying functions and activities that would be more complex otherwise. Even in the medical field, and specifically in oncology, many studies in recent years have highlighted the possible helping role that AI could play in clinical and therapeutic patient management. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Several studies have investigated the application of AI in the treatment and management of advanced melanoma. A review by Guerrisi et al has discussed the application significance and challenges of AI in melanoma treatment but failed to assess the risk of bias and accuracy of existing machine learning models (51). Valenti and colleagues have provided an overview of the application of multi-omics (genomics, transcriptomics, proteomics, metabolomics and radiomics) in evaluating the immunotherapy response of melanoma.…”
Section: Comparison With Previous Reviewsmentioning
confidence: 99%
“…Several studies have investigated the application of AI in the treatment and management of advanced melanoma. A review by Guerrisi et al has discussed the application significance and challenges of AI in melanoma treatment but failed to assess the risk of bias and accuracy of existing machine learning models (51). Valenti and colleagues have provided an overview of the application of multi-omics (genomics, transcriptomics, proteomics, metabolomics and radiomics) in evaluating the immunotherapy response of melanoma.…”
Section: Comparison With Previous Reviewsmentioning
confidence: 99%
“…In oncology, these technologies could allow clinicians to make precision-based predictions, diagnoses, and treatment decisions solely from analyzing patient data. Additionally, these technologies have the potential to improve accuracy, minimize patient sample volume collection, and detect melanoma and metastasis progression earlier [160,161]. For example, Marchetti et al [162] demonstrated the use of an AI algorithm (ADAE) to analyze dermatoscopy images of skin lesions and subsequently predict melanoma risk.…”
Section: Ai and ML Developmentmentioning
confidence: 99%
“…34,35 Others have applied machine learning methods in areas of genetic analysis of metastases, identification of markers associated with disease progression, and even analysis of histologic samples as potential markers for predicting response to therapy. [35][36][37][38] With similar methods, models could be developed to analyze a patient's microbiome composition before ICI therapy initiation. With this information, predictive algorithms could be generated based on the composition and abundance of specific microbial populations to predict whether patients will respond positively to therapy.…”
Section: Use Of Artificial Intelligence For Prediction Of Immunothera...mentioning
confidence: 99%
“…To attempt recommendations on treatments with high efficacy and low adverse effect frequency, the predictive algorithms incorporated information such as age, sex, melanoma type, spontaneous regression, number of invaded lymph nodes, extracapsular extension, mutational status, melanoma stage, number of metastases sites, lines of treatment, and so on. 34,35 Others have applied machine learning methods in areas of genetic analysis of metastases, identification of markers associated with disease progression, and even analysis of histologic samples as potential markers for predicting response to therapy. [35][36][37][38] With similar methods, models could be developed to analyze a patient's microbiome composition before ICI therapy initiation.…”
Section: Use Of Artificial Intelligence For Prediction Of Immunothera...mentioning
confidence: 99%
See 1 more Smart Citation